Research on the mechanism of perceived value of cultural and creative products on consumers’ purchase intention - Xiaofei Lu; Shouwang Li; Zeqian Wang (PLoS ONE, 2026)
In order to resolve the paradox of “high cultural value, low market conversion” and the homogenisation dilemma of cultural and creative products markets, this study proposes an extended analytical framework for cultural and creative products, based on the theory of Customer Perceived Value. The study systematically examines the impact of consumer perceived value on purchase intention from six dimensions: functional quality value, function price value, emotional value, social value, perceptual innovation, perceptual cultural, customer satisfaction, and purchase intention. A questionnaire survey of consumers at the Shaanxi Provincial Museum was conducted, yielding 333 valid responses. These responses were analysed using structural equation modelling. The study revealed that functional quality value, function price value, emotional value, and perceptual innovation all significantly positively influenced customer satisfaction, indirectly driving purchase intent through the full mediation effect of satisfaction. However, the impact of social value did not reach statistical significance. This research challenges the conventional limitations of traditional perceived value models, unveiling a chain mechanism in cultural and creative consumption: The sequence of events leading to the formation of purchase intent is as follows: first, the customer must perceive the value of the product; second, they must be satisfied with this perception. The findings provide a theoretical basis for understanding the pivotal role of cultural value in the transformation of cultural phenomena into market behaviour. The practical implications of this theory suggest that the development of cultural and creative products should move beyond the simple accumulation of symbols. By innovatively designing cultural elements to enhance their perceptibilities and leveraging narrative experiences to improve cultural interpretability, products can strengthen practical functionality and emotional resonance while simultaneously boosting consumers cultural identity and appreciation of innovation. This approach has been demonstrated to effectively activate purchase intent.